Pengembangan Media Pembelajaran Flipchart Berbasis Gamifikasi Untuk Meningkatkan Pemahaman Konsep Pada Materi Hukum Newton - Haryanti, Annisa Bella; Risdianto, Eko; Hamdani, Dedy; Kurniaty, Rikha (Navigation Physics : Journal of Physics Education, 2024)
This research aims to develop innovation in physics education by integrating gamification methods into a flipchart learning media, to assess the suitability of the media, eliciting responses from both students and teachers, and identifying improvements in conceptual understanding. The research methodology employed is Research and Development (R&D) using the ADDIE method. The instruments used include expert validation sheets, pre-test, and post-test sheets, as well as student and teacher response questionnaire sheets. The research results indicate that expert validation yielded an average of 86.25%, meeting the criteria of being highly suitable. This is followed by content suitability at 83.33%, presentation at 87.5%, language at 91.67%, media at 86.90%, and conceptual understanding at 83.33%, demonstrating that all aspects of the assessment criteria are highly suitable. Furthermore, the students' N-Gain shows an average of 0.77, falling within the high criteria. The results of the student and teacher response questionnaire sheets also indicate percentages of 93.03% and 90%, respectively, meeting the criteria of being highly suitable and receiving positive responses after implementation. In conclusion, the gamified flipchart learning media can be utilized to enhance students' conceptual understanding of Newton's laws in the eleventh-grade.